(untitled) (Ustozlar uchun, 2025)
When people learn English, they usually start with grammar. But after some time, they understand that grammar alone is not enough. Words are the real key to communication. If a student knows many words, it becomes easier to speak, write, and understand others. In English, some words feel almost the same, while others feel completely opposite. These word relationships help learners think faster and speak more clearly. This is where synonyms and antonyms become important.